Penerapan Sistem Hubungan Industrial Pancasila Dalam Menyelesaikan Perselisihan Perburuhan Di Indonesia - Na'im, La Ode Aziz; Amrullah, Rezka; Aswandi; Chandra, Mellyana (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This research discusses the application of the Pancasila industrial relations system in resolving labor disturbances in Indonesia, which aims to find out whether the Pancasila industrial relations system is implemented in resolving labor disturbances in Indonesia. The research conducted by researchers used qualitative descriptive methods. Theoretical data collection techniques through library studies in research. Researchers read several written references from journals, articles, books, etc., with the aim of producing a strong theoretical basis for analysis. In qualitative research carried out by researchers, several stages are required in analyzing the data, including; First, Data Reduction, Data Presentation, and Conclusion Drawing. The results of this research show that based on local values in Indonesian society and the history of industrial relations, Indonesia has its own government system called Pancasila Industrial Relations (HIP). However, the position of Pancasila Industrial Relations in Indonesia is currently considered to have not played its maximum role because there are still many problems regarding industrial relations that have arisen and have not been resolved. There are still many factors that trigger conflicts that often occur among workers, namely related to workers' rights, where there are various kinds of problems, including; wages and benefits, working conditions, termination of employment rights (PHK), collective protection, and discrimination in employment.